2020
DOI: 10.1177/0971890720959519
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Tourists’ Behavioural Intentions Towards Use of Select Mobile Wallets for Digital Payments

Abstract: The present study goal is to identify assorted factors and also to investigate their influence on tourists’ behavioural intentions about their usage patterns with respect to M-wallet payment. A conceptual model has been anticipated and authenticated and 600 questionnaires were distributed and 482 were usable. Structural equation modelling was employed to assess research hypotheses. The result shows that the behavioural intention is significantly influenced by perceived value, trust, compatibility and social in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 74 publications
(114 reference statements)
2
20
0
Order By: Relevance
“…Additionally, previous studies found trust as essential driver of technology adoption in context of mobile banking (Alalwan et al, 2017) and mobile learning (Chao, 2019). Recent studies in the context of mobile wallet found significant influence of trust on BIs (Chawla and Joshi, 2020;Hasan and Gupta, 2020).…”
Section: Trustmentioning
confidence: 96%
See 1 more Smart Citation
“…Additionally, previous studies found trust as essential driver of technology adoption in context of mobile banking (Alalwan et al, 2017) and mobile learning (Chao, 2019). Recent studies in the context of mobile wallet found significant influence of trust on BIs (Chawla and Joshi, 2020;Hasan and Gupta, 2020).…”
Section: Trustmentioning
confidence: 96%
“…Extant studies examined the intentions of millennial generation to use the mobile wallets using TAM (Pertiwi et al, 2020). However, Hasan and Gupta (2020) posited that in India there are 135 million e-wallet users, and they have conducted a study with the objective to recognize the determinants of tourists' behavioral intentions to use m-wallet payment with extended TAM model. In the present study, we have applied the TAM model in context of developing nation.…”
Section: Theoretical Background and Development Of Hypothesesmentioning
confidence: 99%
“…Ngubelanga and Duffett [30] investigated the antecedents of customer satisfaction following the use of m-commerce applications by consumers; showing that confidence, social influence, mobility, involvement, and innovation positively influence usefulness and ease of use. Other research has shown that social influence is the main factor in adopting mobile devices and their use as an e-commerce channel [31][32][33][34][35][36][37].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Depending on the domain in which the TAM model is applied, these two main variables are influenced by domain-specific external variables. Our research used the external variables (antecedents) of trust, convenience, customization, innovativeness, rapidity, accessibility, mobility, and enjoyment; variables identified and used in multiple other studies [10,11,[29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][66][67][68][69][70][71][72][73][74][75][76][77][78]. Our theoretical model defines PEU and PU as latent variables influenced by external variables.…”
Section: Research Design and Hypothesismentioning
confidence: 99%
See 1 more Smart Citation